2011
DOI: 10.1590/s1983-14472011000400023
|View full text |Cite
|
Sign up to set email alerts
|

Participação da mulher no processo decisório no ciclo gravídico-puerperal: revisão integrativa do cuidado de enfermagem

Abstract: RESUMOTrata-se de uma revisão integrativa que objetivou identificar a contribuição do cuidado de enfermagem, descrito nas publicações científicas nacionais, para a participação da mulher no processo decisório no ciclo gravídico-puerperal. As produções científicas foram buscadas em maio de 2010, nas bases de dados da Biblioteca Virtual em Saúde. Dos oito artigos que compuseram a revisão, despontaram dois núcleos temáticos: Contribuições do cuidado de enfermagem à participação da mulher no processo decisório no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
8
1
8
Order By: Relevance
“…Health education constitutes an empowerment strategy in nursing care for women undergoing the puerperium, since it is able to promote the adoption of important and beneficial measures for maternal and child health (1) . Educational action is a guiding axis for nursing in the various fields of practice, especially in primary health care services (2) .…”
mentioning
confidence: 99%
“…Health education constitutes an empowerment strategy in nursing care for women undergoing the puerperium, since it is able to promote the adoption of important and beneficial measures for maternal and child health (1) . Educational action is a guiding axis for nursing in the various fields of practice, especially in primary health care services (2) .…”
mentioning
confidence: 99%
“…18 The unpreparedness of some academics and the lack of posture of these and of the health workers about the characteristics of each woman in labor are factors that hurt the privacy and intimacy of these women. 19 The health institution where this study was conducted is considered a teaching hospital and therefore receives many students from various universities and colleges as well as medical residents. This is where these people have the opportunity to practice their knowledge, especially in obstetrics.…”
Section: ] " (Helena)mentioning
confidence: 99%
“…This perspective has also been observed in studies on women's participation in decision-making in pregnancy and childbirth. However, it was identified that the culture of submission establishes the decreased participation and involvement of women in decision-making, in cases that the nurse did not participate actively in the decisions, they do not demonstrate autonomy in activities that involve the context of care (11) . Nurses reveal that the culture of submission in this institution also puts them in a position of submission, in situations of decision-making involving the work of other professionals, mainly physicians.…”
Section: Submission System: Institutionalized Culture and Vision Of Smentioning
confidence: 99%